The Effect of Trust, Transparency, and Security on the Success of Blockchain-Based Decentralized Crowdfunding - Judijanto, Loso; Mardianto, Dedi; Said, Saida (West Science Journal Economic and Entrepreneurship, 2025)
This study examines the effect of trust, transparency, and security on the success of blockchain-based decentralized crowdfunding platforms in Indonesia. Using a quantitative approach, data were collected from 143 participants through a structured questionnaire with a Likert scale ranging from 1 to 5. The collected data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The results show that security and transparency have a significant positive impact on the success of blockchain crowdfunding, while trust also exerts a positive but relatively weaker effect. The findings suggest that ensuring a secure and transparent environment is essential to fostering trust and enhancing the likelihood of success for decentralized crowdfunding platforms. The study contributes to the understanding of critical factors for blockchain crowdfunding success and offers practical implications for platform developers and investors.